2006
DOI: 10.1002/ejlt.200500267
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of volatile compounds and triacylglycerol composition of fatty seed oil gained from flax and false flax

Abstract: Analysis of volatile compounds and triacylglycerol composition of fatty seed oil gained from flax and false flaxLinseed (Linum usitatissimum, L.) and camelina (Camelina sativa, L.) are ancient crops containing seed oils with a high potential for nutritional, medicinal, pharmaceutical and technical applications. In the present study, linseed and camelina oils of plant varieties grown under Central European climate conditions were examined with respect to their volatile and triacylglycerol (TAG) components. Soli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
82
1
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(91 citation statements)
references
References 24 publications
7
82
1
1
Order By: Relevance
“…When the results were compared with the literatures given above, the recorded oil contents and the fatty acids in the present study showed some differences, which can be attributed to several factors, such as growth conditions, genetic factors, geographical variations, and analytical procedures (14).…”
Section: Fatty Acid Compositionsupporting
confidence: 45%
“…When the results were compared with the literatures given above, the recorded oil contents and the fatty acids in the present study showed some differences, which can be attributed to several factors, such as growth conditions, genetic factors, geographical variations, and analytical procedures (14).…”
Section: Fatty Acid Compositionsupporting
confidence: 45%
“…In this work, hexanal, (E)-2-pentenal, heptanal, octanal and (E)-2-heptenal existed in all varieties were considered to enhance flavor quality, most of which were associated with green, sweet, fruity, nutty, oily and fatty odor (Krist et al, 2006). Hexanal was identified as the main volatile compounds in five Camellia seed oils.…”
Section: Resultsmentioning
confidence: 99%
“…The oil has been used for several traditional medicinal purposes. [39] A relatively large proportion of the Linum genome (approximately 3%) comprises 5S-rRNA genes. Intraspecifi c sequence variations among fi ve distinct groups of 5S-rRNA genes indicate that 5S-ribosomal genes most closely resemble other angiosperm 5S genes, while groups 3-5 are highly divergent.…”
Section: Fingerprinting Of Medicinal and Aromatic Plantsmentioning
confidence: 99%